SEVENTY YEARS OF RESEARCH AT THE INSTITUTE OF GEOGRAPHY - DAN BĂLTEANU (Revue Roumaine de Géographie)
The anniversary of a research institute represents not only a significant scientific event but also an emotional one, it is a moment of synthesis of some research directions and of the activity discharged by a whole generation of researchers whose competence and abnegation have contributed to the present scientific level attained by the respective discipline.